The relationship between moral intervention strategies and the stigmatisation of people living with HIV – A Christian perspective - Walt, Izak J. van der (HTS teologiese studies, 2016)
One of the ways in which sexual transmission of AIDS is addressed is through moral interventions by organisations affiliated with Christian churches. However, this approach has been heavily criticised in recent literature, implying that moral interventions by church-affiliated organisations generally lead to stigmatisation which is one of the major obstacles to their involvement in HIV prevention. This article explores the origin of this accusation and discusses the Christian-ethical aspects related to HIV or AIDS. The conclusion is that the fact that churches take the Word of God and Christian morality as point of departure in HIV or AIDS intervention programmes does not imply that people who transgressed religious moral teachings may be condemned. On the contrary, the church preaches Christian forgiveness, mercy and empathy. Churches and organisations affiliated with churches should therefore be regarded as valuable partners in the fight against AIDS, for while propagating a normative lifestyle, they also preach love, compassion and support for people living with HIV.